Experimental Conditions to Obtain Photopolymerization Induced Phase Separation Process in Liquid Crystal-Photopolymer Composite Materials under Laser Exposure - Manuel Ortuño; Andrés Márquez; Sergi Gallego; Inmaculada Pascual; Augusto Beléndez (International Journal of Polymer Science)
We analyze the experimental conditions necessary to obtain a photopolymerization induced phase separation process inside liquid crystal-photopolymer composite materials. Composites stored for 24 hours perform poorly in hologram recording but a good result is obtained if they are used recently prepared. We use a procedure combining heat and sonication to disarrange the liquid crystal structures formed during storage of the composite. We also propose incoherent light treatment after recording the hologram in order to evaluate if the phase separation evolved correctly during hologram recording.